CA19-9 and CEA biosensors in pancreatic cancer - Ahmadipour M.; Bhattacharya A.; Sarafbidabad M.; Syuhada Sazali E.; Krishna Ghoshal S.; Satgunam M.; Singh R.; Rezaei Ardani M.; Missaoui N.; Kahri H.; Pal U.; Ling Pang A. (Elsevier B.V., 2025)
Cancer is a complex pathophysiological condition causing millions of deaths each year. Early diagnosis is essential especially for pancreatic cancer. Existing diagnostic tools rely on circulating biomarkers such as Carbohydrate Antigen 19?9 (CA19-9) and Carcinoembryonic Antigen (CEA). Unfortunately, these markers are nonspecific and may be increased in a variety of disorders. Accordingly, diagnosis of pancreatic cancer generally involves more invasive approaches such as biopsy as well as imaging studies. Recent advances in biosensor technology have allowed the development of precise diagnostic tools having enhanced analytical sensitivity and specificity. Herein we examine these advances in the detection of cancer in general and in pancreatic cancer specifically. Furthermore, we highlight novel technologies in the measurement of CA19-9 and CEA and explore their future application in the early detection of pancreatic cancer. ? 2024 Elsevier B.V.